The Potential of Trichoderma sp. as a Decomposer of Cocoa Pod Husk- Based Compost on Degradation of Herbicide and Insecticide Residues - Perdana, Andrian; Puspita Sari, Niken (Indonesian Coffee and Cocoa Research Institute, 2025)
Compost, a final product of composting as a sustainable waste management strategy, contains a wide range of organic pollutants penetrating by deliberate input such as pesticide application in feedstock materials. The involvement of Trichoderma in composting processes is expected to degrade pesticide compounds and enhance compost quality. The study employed four treatments: P1D0 (herbicide without Trichoderma sp.), P1D1 (herbicide with Trichoderma sp.), P2D0 (insecticide without Trichoderma sp.), and P2D1 (insecticide with Trichoderma sp.). The results of pesticide residue and compost quality were analyzed descriptively by comparing the effects of Trichoderma sp. n degrading the herbicide and insecticide residue through the composting process. Compost quality was monitored through initial, biweekly, and final analyses. All compost fulfilled the minimum standards set by the Indonesian Ministry of Agriculture. Incorporation of Trichoderma sp. enhanced compost quality by increasing N content (up to 37.23%) and pH (up to 5.28%), while reducing the C:N ratio (up to 50%). Moreover, it effectively degraded glyphosate and cypermethrin residues by up to 99.96% and 99.48%, respectively. These findings highlight the dual role of Trichoderma-enriched compost in improving compost quality and remediating pesticide residues, supporting sustainable and environmentally friendly agricultural practices.